Polyampholyte Hydrogels with pH-Dependent Swelling for Controlled Catch and Release of Model Dyes - Çeper, Tolga; Mohotti, Supun W.; Lange, Leon X.; Schacher, Felix H. (Organic Materials, 2024)
Polyampholyte hydrogels with tunable charge are synthesized by a facile two-step approach including the free-radical crosslinking copolymerization of tert-butoxycarbonylaminomethylacrylate (tBAMA) with N,N′-methylenebisacrylamide and subsequent deprotection. Thermal, photo- and redox-initiating methods were utilized in the synthesis of crosslinked PtBAMA and the resulting polymer networks swell during deprotection in a mixture of trifluoro acetic acid/water. While the crosslinked PtBAMA forms organogels in various organic solvents such as chloroform, acetone and DMSO, polydehydroalanine (PDha) networks after deprotection form hydrogels with pH-dependent swelling and oscillatory swelling/deswelling depending on pH value and salinity. The tunable charge of the developed hydrogels was employed for a catch-and-release platform controlled by pH, in which methylene blue as a cationic model was adsorbed at pH 11 and desorbed at pH 2, whereas methyl blue as an anionic model dye was adsorbed at pH 2 and desorbed at pH 11.
Keywords: polyampholyte hydrogels; charge tuning; pH-responsive hydrogels; catch-and-release